2014
DOI: 10.1016/b978-0-12-800267-4.00006-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mast Cells and Importance of Their Tryptase and Chymase Serine Proteases in Inflammation and Wound Healing

Abstract: Mast cells (MCs) are active participants in blood coagulation and innate and acquired immunity. This review focuses on the development of mouse and human MCs, as well as the involvement of their granule serine proteases in inflammation and the connective tissue remodeling that occurs during the different phases of the healing process of wounded skin and other organs. The accumulated data suggest that MCs, their tryptases, and their chymases play important roles in tissue repair. While MCs initially promote hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 242 publications
2
125
0
Order By: Relevance
“…However, there is a claim that a third subset -only chymase-positive mast cells (MC C ) -exists [8] or even there is a wider spectrum of MCs subgroups, varying in the number and types of mediators they produce when activated [3]. In the skin, the MC TC population predominates [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is a claim that a third subset -only chymase-positive mast cells (MC C ) -exists [8] or even there is a wider spectrum of MCs subgroups, varying in the number and types of mediators they produce when activated [3]. In the skin, the MC TC population predominates [9].…”
Section: Introductionmentioning
confidence: 99%
“…in the intestinal mucosa and in the skin. In normal conditions they are found in subcutaneous fat and dermis, near blood vessels, hair follicles and nerves [2,3]. They contain granules with a vast array of mediators, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chymase secreted by mast cells is a type of serine protease and its release activates transforming growth factor (TGF)-β1 via paracellular secretion stimulation and fibrinolysin (3)(4)(5). A previous study demonstrated that chymase has a potential role in tissue fibrosis (6).…”
Section: Introductionmentioning
confidence: 99%